Lightweight, thermally insulating and stiff carbon honeycomb-induced graphene composite foams with a horizontal laminated structure for electromagnetic interference shielding. (October 2017) - Yuan, Ye; Liu, Liyang; Yang, Minglong; Zhang, Tieliang; Xu, Fan; Lin, Zaishan; Ding, Yujie; Wang, Chunhui; Li, Jianjun; Yin, Weilong; Peng, Qingyu; He, Xiaodong; et al.
Abstract: In this study, lightweight but stiff carbon monolith with unique laminated inner structure for high electromagnetic interference (EMI) shielding is designed and prepared. The carbon monolith is consisting of carbon honeycomb structure which was filled with a horizontal laminated reduced graphene foam structure that is perpendicular to the cell wall. The stiff carbon honeycomb (CH) structure not only acts as a conductive and load-bearing framework, but also as the induced source for the growth of ice crystals to make a highly aligned laminated structure in the reduced graphene oxide (rGO) foam, by utilizing the big difference in thermal conductivity between air and the carbon cell wall. Consequently, a EMI shielding effectiveness of around 36–43 dB and remarkable specific EMI shielding effectiveness of 688.5 dB cm 3 g −1 in the X-band is achieved. More importantly, the addition of CH structure significantly increases the compressive stress of rGO foam to 2.02 MPa, almost which is 6760 times higher than common rGO foam. Moreover, the carbon monolith shows a thermal conductivity of 0.057 W/(m·K) and exhibits good flame retardancy. These results indicate that the carbon monolith is an ideal component for high-performance EMI shielding material, which has great potential applications in aviation and the aerospace industry. Graphical abstract: